Estimating a fiscal reaction function for Nigeria - Patricks Ogiji; Kayode J. Ajayi (CBN Journal of Applied Statistics, 2020)
The study examines the determinants of fiscal balance and the impact of the selected macroeconomic variables on the primary balance of government. It aims to estimate the fiscal reaction function for Nigeria and determine whether the implementation of fiscal policy is sustainable in the long-run. A Fiscal Reaction model was developed and ARDL technique was used to establish the relationships and interactions among the variables. The study investigated whether the fiscal measures pursued by the government from 2000:Q1 to 2018:Q4 was adequate in addressing the accumulation of huge debt. The analysis of the stylized facts reveals that the government had continued to run budget deficits for almost the entire period, except for a few period. The public debt to GDP, which is a major determinant of the primary balance, is negative and significant implying that a fiscal rule that encourages a strong reduction indebt-to-GDP levels would result in substantial pressure for Nigeria to run large primary surpluses in the future. The CUSUM and CUSUMSQ tests show the recursive residual plots of the fiscal reaction function are within the 5 per cent critical lines, hence, providing evidence of stable fiscal reaction function for Nigeria. The study thus, recommends that, apart from the urgent need for the fiscal authorities to adopt urgent reforms to discourage huge debt accumulation, improve revenue generation capacity and more fundamentally, expenditure switching to improve the quality of expenditure, the transition from primary deficits to primary surpluses should follow a gradual process.
Keywords: E62; H62; H63; H39; 330; Fiscal Reaction Function; ARDL Model; Debt; Revenue